Informing the development of an Internet-based chronic pain self-management program. (January 2017) - Gogovor, Amédé; Visca, Regina; Auger, Claudine; Bouvrette-Leblanc, Lucie; Symeonidis, Iphigenia; Poissant, Lise; Ware, Mark A.; Shir, Yoram; Viens, Natacha; Ahmed, Sara
Highlights: Internet-based self-management programs may help to address gaps in chronic pain management. Interactivity, personalization and tailored messages are minimum features for self-management web portal. Non-medical information is as important as medical information. Abstract: Background: S elf-management can optimize health outcomes for individuals with chronic pain (CP), an increasing fiscal and social burden in Canada. However, self-management is rarely integrated into the regular care (team activities and medical treatment) patients receive. Health information technology offers an opportunity to provide regular monitoring and exchange of information between patient and care team. Objective: To identify information needs and gaps in chronic pain management as well as technology features to inform the development of an Internet-based self-management program. Methods: Two methods were used. First was a structured literature review: electronic databases were searched up to 2015 with combinations of MeSH terms and text-words such as chronic pain, self-management, self-efficacy, technology, Internet-based, patient portal, and e-health. A narrative synthesis of the characteristics and content of Internet-based pain management programs emerging from the literature review and how they relate to gaps in chronic pain management were completed. Second, four audiotaped focus group sessions were conducted with individuals with chronic pain and caregivers (n = 9) and health professionals (n = 7) recruited from three multidisciplinary tertiary and rehabilitation centres. A thematic analysis of the focus group transcripts was conducted. Results: Thirty-nine primary articles related to 20 patient-oriented Internet-based programs were selected. Gaps in CP management included lack of knowledge, limited access to health care, suboptimal care, and lack of self-management support. Overall, 14 themes related to information needs and gaps in care were identified by both health professionals and patients, three were exclusive to patients and five to health professionals. Common themes from the focus groups included patient education on chronic pain care, attitude-belief-culture, financial and legal issues, end-of-program crash, and motivational content. Conclusions: Internet-based programs contain automated, communication and decision support features that can address information and care gaps reported by patients and clinicians. However, focus groups identified functionalities not reported in the literature, non-medical and condition- and context-specific information, integration of personal health records, and the role of the different health professionals in chronic pain management were not identified. These gaps need to be considered in the future development of Internet-based programs. While the association between the mechanisms of Internet-based programs' features and outcomes is not clearly established, the results of this study indicate that interactivity, personalization and tailored messages, combined with therapist contact will maximize the effectiveness of an Internet-based chronic pain program in enhancing self-management.